IMPLEMENTASI PASAL 20 UNDANG-UNDANG NOMOR 10 TAHUN 2009 TENTANG KEPARIWISATAAN TERHADAP HAK-HAK WISATAWAN DI OBJEK WISATA PANTAI JAKAT BENGKULU - mardayanti, syakina; Ganefi, Ganefi; Sofyan, Tito (Jurnal Ilmiah Kutei, 2023)
Tourism is one of the largest sectors that have an influence on economic growth in Indonesia. In order to be managed properly the Government regulates into Law Number 10 of 2009 concerning Tourism with the aim of providing boundaries and directions for the realization of tourism progress. One of the leading tours in Bengkulu Province is Jakat Beach with a beautiful panoramic view of the ocean. Apart from the natural beauty that is provided, of course, legal protection for tourists must be prioritized so that no losses can be experienced by tourists. This study aims to analyze the implementation of Article 20 of Law Number 10 of 2009 concerning Tourism in Bengkulu Jakat Beach Tourism Objects that cannot be carried out optimally and what solutions can be done in order to protect tourists at Bengkulu Jakat Beach attractions. The type of research used is empirical research. Based on the results obtained in this study that the rights of tourists have not been maximally implemented due to lack of legal awareness from various parties involved, however, management and development and improvement of tourism will always be carried out. Efforts that can be made are by increasing cooperation between stakeholders, business actors and tourists as well as increasing legal awareness and tourism awareness. Keywords: implementation, protection, tourist rights